2019
DOI: 10.1029/2017rg000594
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Detection of Explosive Events

Abstract: The ionospheric response to explosions which occur at or below the Earth's surface has been noted since the first detonations of nuclear devices during the early period of aboveground testing. Acoustic gravity waves and traveling ionospheric disturbances were detected in association with test explosions carried out by the Union of Soviet Socialist Republics in Novaya Zemlya in 1961. While research in this area has continued, the standards accepted by the Comprehensive Nuclear Test Ban Treaty for detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 151 publications
0
37
0
Order By: Relevance
“…Huang et al () have recently provided an extended review on ionospheric detection of explosive events. The current review article is exclusively targeted at ionospheric detection of such natural hazards as earthquakes, tsunamis, and volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al () have recently provided an extended review on ionospheric detection of explosive events. The current review article is exclusively targeted at ionospheric detection of such natural hazards as earthquakes, tsunamis, and volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this need, it has recently been suggested that the ionosphere-based technique could, in future, present a novel approach for NH-detection in near-real time (e.g., Savastano et al, 2017). Huang et al (2019) have recently provided an extended review on ionospheric detection of explosive events. The current review article is exclusively targeted at ionospheric detection of such natural hazards as earthquakes, tsunamis, and volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…The ionospheric disturbances due to explosions have been identified with ionosondes (e.g., Beynon & Jones, ; Dieminger & Kohl , ; Gardiner , ; Hines, ), Doppler sounders (Jacobson et al, ; Blanc & Jacobson, ; Blanc & Rickel, ; Krasnov & Drobzheva, ), and GPS‐bases TEC measurements (Calais et al, ; Fitzgerald & Carlos , ; Park et al, , ; Yang et al, ; Zhang & Tang, ). Both atmospheric acoustic and gravity wave signatures have been observed (Huang et al, ). For explosions above the ground, the generation of atmospheric acoustic‐gravity waves can be explained by the same mechanisms as for volcanic eruptions.…”
Section: Summary Of Major Observational Resultsmentioning
confidence: 99%
“…Moderate and small surface disturbance events may well generate weak upper atmospheric signatures that could be comparable to the noise level of some of the existing observational techniques. This could motivate the development and application of more precise upper atmospheric monitoring techniques and systems, for instance, radio frequency interferometry measurements (Huang et al, ). How the upper atmospheric response varies with the state of the background atmosphere is a fundamental question to address. For instance, the background neutral wind has a significant influence on the propagation of atmospheric acoustic‐gravity waves.…”
Section: Most Recent Advances and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation